Social, financial and psychological stress during an emerging pandemic: observations from a population survey in the acute phase of COVID-19. Issue 12 (12th December 2020) - Robillard, Rebecca; Saad, Mysa; Edwards, Jodi; Solomonova, Elizaveta; Pennestri, Marie-Hélène; Daros, Alexander; Veissière, Samuel Paul Louis; Quilty, Lena; Dion, Karianne; Nixon, Ashley; Phillips, Jennifer; Bhatla, Raj; et al.
Abstract : Introduction: The negative impacts of COVID-19 have rippled through every facet of society. Understanding the multidimensional impacts of this pandemic is crucial to identify the most critical needs and to inform targeted interventions. This population survey study aimed to investigate the acute phase of the COVID-19 outbreak in terms of perceived threats and concerns, occupational and financial impacts, social impacts and stress between 3 April and 15 May 2020. Methods: 6040 participants are included in this report. A multivariate linear regression model was used to identify factors associated with stress changes (as measured by the Cohen's Perceived Stress Scale (PSS)) relative to pre-outbreak retrospective estimates. Results: On average, PSS scores increased from low stress levels before the outbreak to moderate stress levels during the outbreak (p<0.001). The independent factors associated with stress worsening were: having a mental disorder, female sex, having underage children, heavier alcohol consumption, working with the general public, shorter sleep duration, younger age, less time elapsed since the start of the outbreak, lower stress before the outbreak, worse symptoms that could be linked to COVID-19, lower coping skills, worse obsessive–compulsive symptoms related to germs and contamination, personalities loading on extraversion, conscientiousness and neuroticism, left wing political views, worse family relationships and spending less time exercising and doing artistic activities. Conclusion: Cross-sectional analyses showed a significant increase from low to moderate stress during the COVID-19 outbreak. Identified modifiable factors associated with increased stress may be informative for intervention development. Trial registration number: NCT04369690 ; Results.